Court rejects UUMs bid: University ordered to pay RM3.7m to KIC Management - The Edge Financial Daily (The Edge Financial Daily, 2012)
ALOR STAR: Universiti Utara Malaysia's (UUM) application to suspend an execution of judgment was rejected and the university was ordered to pay more than RM3.7 million to KIC Management Sdn Bhd for breaching an agreement to outsource a master's degree programme to the company.